2021
DOI: 10.1108/bfj-07-2020-0622
|View full text |Cite
|
Sign up to set email alerts
|

The role of intrinsic and extrinsic characteristics of honey for Italian millennial consumers

Abstract: PurposeThis study aims to examine the importance that different intrinsic and extrinsic attributes represent for young Italian consumers of honey, analysing how these aspects influence the quality perceived during consumption. In addition, demographic and lifestyle aspects have been considered as possible discriminants influencing millennial generation honey consumers.Design/methodology/approachThe authors performed a non-parametric rank-based test (Mann–Whitney U test) to analyse which attributes millennials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
4
14
0
1
Order By: Relevance
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
“…These certified products outside their "area of influence" may not have the emotional attachment of experience [31,33]. Studies measuring the awareness and recognition of quality labels among European consumers conclude that consumers from Sweden, Denmark, Finland, and the Netherlands, but also France, Italy, Spain, Greece, Portugal have a higher likelihood of recognizing quality labels and their logos [34,35]. This is due to the collaborative activities between European producers, which target consumers in these countries.…”
Section: Preference Recognition and Willingness To Pay For Certified Agri-food Productsmentioning
confidence: 99%
“…Żak (2017) highlights the main factors taken into consideration by young consumers when buying honey, namely its price and the sensorial features. On assessing the factors influencing the honey-purchasing process of the alleged millennial generation, Blanc et al (2021) single out perceptions that are firstly concerned with sustainability, preserving resources and environment. Further, they evaluate a series of features that have the final say when buying honey such as ecological footprint which contributes significantly to the development and support of a healthy lifestyle (Blanc et al, 2021).…”
Section: Factors Which Influence Honey Purchasing Behaviourmentioning
confidence: 99%
“…Most scientific studies report the prevalence of honey adulteration and focus on the latest most advanced honey authenticity detection method (Fakhlaei et al, 2020;Se et al, 2019;Soares et al, 2017). From a commercial standpoint, there is an abundance of studies assessing consumers' honey preferences and honey's criteria affecting their purchase decision (Batt & Liu, 2012;Blanc et al, 2021;Kallas et al, 2019;Murphy et al, 2000). However, little is known about consumers' understanding and awareness about the issue of fraudulent honey, as such, insight on the level of consumer awareness about fraudulent honey and the effect of awareness on their intention to purchase fraudulent honey warrant further investigation.…”
Section: Problem Statementmentioning
confidence: 99%